Phase transformation and mechanical properties of heat-treated nickel-titanium rotary endodontic instruments at room and body temperatures - Yuka Kasuga; Shunsuke Kimura; Keiichiro Maki; Hayate Unno; Satoshi Omori; Keiko Hirano; Arata Ebihara; Takashi Okiji (BMC, 2023)
Abstract Background The aim of this study was to evaluate the phase composition, phase transformation temperatures, bending property, and cyclic fatigue resistance of different heat-treated nickel-titanium (NiTi) rotary instruments with the same tip diameter and taper at room (RT; 25 ± 1 °C) and body (BT; 37 ± 1 °C) temperatures. Methods Five heat-treated NiTi rotary instruments, HyFlex EDM (EDM), HyFlex CM (CM), Vortex Blue (VB), RE file CT (RE) and JIZAI, and a non-heat-treated NiTi rotary instrument (Mtwo) with a size 40, 0.04 taper were investigated. Temperature-dependent phase transformation was examined with differential scanning calorimetry (DSC). The bending loads of the instruments at RT and BT were evaluated using a cantilever-bending test. Cyclic fatigue resistance at RT and BT was measured using a dynamic test, during which the instruments were rotated in combination with a 2-mm back-and-forth motion in an artificial curved canal, and the number of cycles to failure (NCF) was determined. The results were analyzed using two-way repeated measures analysis of variance, a simple main effect test, and the Bonferroni test (α = 0.05). Results DSC results indicated that EDM and Mtwo were primarily composed of martensite/R-phase and austenite, respectively, while the other heat-treated instruments were composed of a mix of martensite/R-phase and austenite at the tested temperatures. Regardless of the temperature setting, the bending loads of heat-treated instruments were significantly lower than those of Mtwo (p < 0.05). EDM showed the lowest bending loads and highest NCF at both temperatures (p < 0.05). CM, VB, and JIZAI showed significantly higher bending loads at BT than at RT (p < 0.05). The NCF of all the heat-treated instruments, except VB, was lower at BT than at RT (p < 0.05). At BT, the NCF of CM, VB, RE, and JIZAI were not significantly higher than that of Mtwo (p > 0.05). Conclusions Heat-treated NiTi instruments exhibited lower bending loads and higher NCF values than Mtwo. However, this tendency was less pronounced at BT than at RT, especially in the NCF values of instruments with a mixture of martensite/R-phase and austenite phases at the tested temperatures.